Do anabolic-androgenic steroids enhance sporting performance? - Kennedy, M. C.; O'Sullivan, A. J. (The Medical Journal of Australia, 1997)
On considering the available evidence, it appears that anabolic steroids definitely increase muscle size, and probably strength, but the mechanism is unknown. Further studies, using a crossover design, including inexperienced as well as experienced weightlifters, and the same drug vehicle for both placebo and active drug, with confirmation of subject blinding, should probably be conducted to confirm these findings. In addition, whether androgen-induced muscle hypertrophy translates into improved performance in sports that require skill as well as strength remains to be determined. But such studies should not overshadow the need for significant research into the prevention of anabolic-androgenic steroid abuse.